Bridging scholarly theory and forensic practice: toward a more pedagogical model of rhetorical criticism - Ott, Brian L., author; National Forensic Association, publisher (Colorado State University. Libraries, 1998)
In this essay, the author contends that competitors in the event of rhetorical criticism, or communication analysis (CA) as it is alternatively called, are locked into a model that poses serious questions about the educational value of the event. In an effort to narrow the ever widening gap between theory and practice and to heighten the pedagogical value of contest rhetorical criticism, the author proposes to chart briefly the chief features of the existing RC model, to identify the limitations posed by that model, and to suggest several viable alternatives.
Brian Ott was a professor in the Department of Speech Communication at Colorado State University.
Keywords: CA; communication analysis; rhetorical criticism; forensic practice; RC model